Esophageal squamous cell carcinomas in a Malaysian cohort show a lack of association with human papillomavirus - Cheah, Phaik Leng; Koh, Cing Chai; Khang, Tsung Fei; Goh, Khean Lee; Lau, Peng Choong; Chin, Kin Fah; Teoh, Kean Hooi; Toh, Yen Fa; Looi, Lai Meng (Wiley, 2018)
OBJECTIVE: With an age-standardized incidence rate of 2 per 100 000, esophageal cancer is not common among Malaysians, but they are nevertheless important due to its poor prognosis. The study is to clarify whether the human papillomavirus (HPV) is associated with esophageal cancer in Malaysians as there has been no report to date on this in Malaysians and other South East Asians. METHODS: Altogether 67 esophageal squamous cell carcinomas histologically diagnosed between 1 January 2004 and 31 December 2014 at the Department of Pathology, University of Malaya Medical Center, Malaysia were considered for HPV analysis using two commercially available methods, polymerase chain reaction with flow-through hybridization (21 HPV GenoArray Diagnostic Kit) and multiplex real-time polymerase chain reaction (Anyplex II HPV28 Detection). The DNA amplifiability of the formalin-fixed, paraffin-embedded tumor was checked by amplification of a 268 bp segment of the human β-globin gene (GH20/PC04) prior to HPV detection. RESULTS: HPV detection was finally carried out in 51 patients. HPV16 was detected in the moderately differentiated, stage IV lower esophageal tumor of a 32-year-old Malaysian-born Chinese woman by both methods. Except for a predilection for Indians, the clinical characteristics of esophageal squamous cell carcinomas in this Malaysian cohort were generally similar to those of other populations. CONCLUSION: It appears that HPV is rare and an unlikely oncovirus in esophageal squamous cell carcinomas of Malaysians.